"An exercise in careful diplomacy": talking about alcohol, drugs and family violence. Issue 3 (3rd July 2019) - Yates, Sophie
Abstract: The role of alcohol and drugs (AOD) in domestic and family violence is increasingly difficult to ignore, yet challenging to reconcile with dominant feminist analyses of the problem. The landmark 2015–16 Victorian Royal Commission into Family Violence recommended service integration between the AOD and domestic and family violence (DFV) sectors, but this may be difficult to achieve due to differences in history, language use and treatment philosophy between the two sectors. A central point of contention about the role of AOD in DFV can be represented by the question: "are alcohol and other drugs a cause of DFV?" Unpacking this question is essential to understanding contested problem framing in this area, and requires attention to differences in language use and research traditions; varying acceptance of gender inequity as a central causal factor; cultural attitudes about alcohol and disinhibition; and notions of accountability across the different sectors. I argue that substance abuse affects DFV in gendered ways, and that more attention should be paid to how AOD and gender intersect to affect the perpetration and experience of DFV. This article will be useful to practitioners seeking to understand the sensitivities surrounding discussion of AOD in relation to DFV, and will assist them in navigating these sensitivities to improve service coordination and thus deliver better outcomes for those affected by DFV.